HOME GARDENS AND FOOD SECURITY: AN ECONOMIC ANALYSIS IN LAMDINGIN, BANDA ACEH - Ade Elvi Rahmah (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2026)
Abstract: This study analyzes the utilization of homegarden land in Lamdingin Village, Kuta Alam Sub-District, Banda Aceh City, as a strategy to enhance household food security and economic resilience. The research objectives are: (1) to identify the potential of homegardens as sources of food and income, (2) to evaluate community knowledge and skills in their management, and (3) to reveal major constraints and propose alternative solutions. A descriptive approach was employed, utilizing a survey method targeting households owning homegardens. Data collected encompassed homegarden characteristics, cultivated commodity types, utilization of produce (for consumption and/or sale), and technical and non-technical barriers. Findings indicate substantial potential for homegarden development through the cultivation of vegetables, fruits, and small livestock, supporting family nutritional needs and generating supplementary income. However, utilization remains limited due to constrained land availability, inadequate technical knowledge, scarcity of production inputs, and disruptions from pests and plant diseases. Keywords: Homegarden land; Household food security; Vegetables; Fruits; Household agribusiness